Physical activity and dietary patterns: a health risk behavior cluster pattern analysis of students in a Caribbean medical school - Nauhria, Samal; Das, Sanjib; Alsalhanie, Kusai M; Goyal, Anmol; Gupta, Brijinder K; Akinboboye, Olawole; Ehwarieme, Oghenetega (Asian Journal of Medical Sciences, 2017)
Background: Collegial effects of variable lifestyle risk behaviors on the high incidence of chronic conditions are pivotal issues in defining overall health and public wellness. Medical students are expected to have a superior understanding of health issues but the majority of them lead an unhealthy lifestyle. Aims and Objectives: This study examined the prevalence and clustering patterns of multiple health risk behaviors among students of a Caribbean medical school. Materials and Methods: A cross-sectional study was conducted among the first and second-year medical students by using questionnaire which assessed multiple health behaviors including physical activity patterns, fruits, vegetables and breakfast consumption. Age and gender specific clustering patterns of various risk behaviors were identified. Results: Study suggested that male students were more active than female students (p<0.01). Gender non-specific younger age group was more active than older age group (p<0.001). The frequency of breakfast consumption was higher in males (p<0.01). Fruit & vegetable consumption was higher in older students (p<0.01) irrespective of gender. A cluster of three health risk behavior was found in 10% of the total students while only 7% met the recommendations for all three health risk behaviors. BMI of the majority of students (72%) was found to be within normal range. The primary motivation for performing physical activity in 35% students was to lose weight or maintain appearance and in 31% to eliminate stress. Conclusion: Many medical students still fail to meet the physical activity and dietary recommendations which may be attributed to their busy schedules and academic overload. Asian Journal of Medical Sciences Vol.8(4) 2017 50-56